1998
DOI: 10.1111/j.1398-9995.1998.tb03911.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationships between environmental factors (aeroallergens, air pollution, and weather) and asthma emergency admissions to a hospital in Mexico City

Abstract: There have been several studies of the relationships between environmental factors, particularly air pollution, and attacks of asthma. Most of these studies have ignored the potential confounding effects of aeroallergens such as pollens and fungal spores. We report a statistical analysis of the relationships between emergency admissions for asthma to a hospital in Mexico City and daily average airborne concentrations of pollen, fungal spores, air pollutants (O3, NO2, SO2, and particulates) and weather factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
93
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 33 publications
8
93
1
2
Order By: Relevance
“…Rosas et al (1998 ) and Salvaggio et al (1971 ) found significant associations between asthma ED visits and both pollens and fungal spores in Mexico City and New Orleans, respectively. In studies in Ottawa, Canada, San Diego, California, and State College, Pennsylvania, asthma ED visits, asthma severity and peak flow decrements, respectively, were associated with fungal spores but not pollens (Dales et al, 2000;Delfino et al, 1996;Neas et al, 1996 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rosas et al (1998 ) and Salvaggio et al (1971 ) found significant associations between asthma ED visits and both pollens and fungal spores in Mexico City and New Orleans, respectively. In studies in Ottawa, Canada, San Diego, California, and State College, Pennsylvania, asthma ED visits, asthma severity and peak flow decrements, respectively, were associated with fungal spores but not pollens (Dales et al, 2000;Delfino et al, 1996;Neas et al, 1996 ).…”
Section: Discussionmentioning
confidence: 97%
“…In another study in Mexico city, which also considered aeroallergens (see below ) , ozone was positively associated with asthma ED visits by adults in the dry season (January to April, November, December ) in a model that also included grass pollen and SO 2 , whereas SO 2 was positively associated with visits by seniors in the wet season ( May to October ) in a model that also included PM 10 and tree pollen ( Rosas et al, 1998 ) . In a study by Rossi et al ( 1993 ) in Oulu Finland, which also examined the effects of both pollens and air pollution on asthma ED visits, NO 2 was the only significant predictor among pollutants, based on a stepwise procedure that also considered H 2 S, SO 2 and TSP.…”
Section: Discussionmentioning
confidence: 99%
“…However, laboratory experiments were not able to reproduce what happens under the much more complex natural conditions, where the influence of these phenomena may be enhanced by air contaminants, infecting agents, or particles causing allergy or irritation (Rosas et al, 1998;Galán et al, 2000). There is now evidence of a worldwide increase in the occurrence of asthma and other allergic diseases, especially in industrial societies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on exposure of air pollution and its association with health, but inconsistent results have been reported regarding its association with asthma rate. Though most of the studies have pointed out that air pollution triggers the asthma rate; few have reported that there is no correlation between air pollution and asthma rate (Rosas et al, 1998;Dales et al, 2000;Chen et al, 2004). Asthma is a chronic disease linked with considerable morbidity, mortality, and health care use.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies of air pollution have used time-series analysis to relate daily asthma rates to daily air pollution levels for short-term associations between air pollution and health. A substantial number of epidemiological studies reported associations between mortality/morbidity with air pollution levels (Rosas et al, 1998;Dales et al, 2000;Levy et al, 2000;Chen et al, 2004;Goodman et al, 2004;Pope et al, 2004;Schwartz, 2004;Chang et al, 2005;Analitis et al, 2006;Dominici et al, 2006;Hinwood et al, 2006;Yang et al, 2007;Yang, 2008;Halonen et al, 2008;Chiu et al, 2009;Halonen et al, 2009;Belleudi, 2010;Hsieh et al, 2010;Gorai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%